2019
DOI: 10.1177/0022343318808347
|View full text |Cite
|
Sign up to set email alerts
|

Energy resources and the risk of conflict in shared river basins

Abstract: This study examines the effect of energy resources on the chances for militarized conflict, water related conflict and cooperation events, and cooperative river treaties between pairs of states on shared international river basins. We examine trade-offs that riparian states can make between energy resources such as oil or natural gas and fresh water resources. Integrating upstream and downstream states’ geographical position in a river basin with energy resource information, we examine four related scenarios o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 59 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…Using this dataset, Hatipoglu et al 2018found that trade of energy resources, and natural gas in particular, leads to more cordial relations between two states. In a similar vein, Lee and Mitchell (2019) showed that when producing notable hydroelectric power from a river themselves, downstream states prefer more cordial relations with upstream states.…”
Section: Renewables and Energy Trade: A New Form Of Interdependence?mentioning
confidence: 91%
“…Using this dataset, Hatipoglu et al 2018found that trade of energy resources, and natural gas in particular, leads to more cordial relations between two states. In a similar vein, Lee and Mitchell (2019) showed that when producing notable hydroelectric power from a river themselves, downstream states prefer more cordial relations with upstream states.…”
Section: Renewables and Energy Trade: A New Form Of Interdependence?mentioning
confidence: 91%
“…Islam and Gnauck (2009) have analyzed threats to mangrove wetland ecosystems in the Ganges basin. Kedzior (2017) has analyzed environmental awareness and participation in Ganges water quality policy in India, and Lee and Mitchell (2019) have analyzed water related conflicts with reference to the Ganges basin. More generally, sustainability considerations, broadly construed, in the context of rivers have been studied by Ferrer et al (2022), Xu et al (2022), andAnh et al (2022).…”
Section: Objectivesmentioning
confidence: 99%